Interpreter Training: Nonverbal Communication and the Interpretative Process - Seijo Fernández, Raquel; Soto Aranda, Beatriz (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper’s focus is placed on interpreting training, offering teaching techniques that allow students to master the analysis, understanding and proper use of nonverbal communication. More specifically, it addresses the importance of paralanguage (that is, our voice and its characteristics) in the interpretation process, its influence on the verbal message and the relevance of its proper use in order to offer an accurate interpretation that keeps the intention and sense of the original message. A series of basic exercises for the development of the interpreting technique are offered as well.